«Я расскажу вам историю»… (роман Дженет Уинтерсон Хозяйство света) - Natalia Wladimirowa (Polilog: Studia Neofilologiczne, 2012)
“I’ll tell you a story…” (the novel Lighthousekeeping by Jeanette Winterson)